2005
DOI: 10.1089/dia.2005.7.710
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of an Automated Wireless Messaging System for Diabetes

Abstract: Utilizing a wireless, automated messaging system in clinical practice is a feasible, low-cost, interactive way to facilitate diabetes self-management, which is acceptable to patients. While providing a convenient way for patients and providers to communicate, this system can support automated recording and ready retrieval of these real-time interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…In a recent study, a two-way paging system sent an average of 3.2 messages per day. 30 In our cell phone group, users responded to 16.6% of reminders, similar to the 14% response rate in the pager study. Thus, it seems unrealistic to expect users to respond to every message received, although participants could have checked their BG level in response to the reminder prompt even if they did not reply to the reminder.…”
Section: Figsupporting
confidence: 69%
See 1 more Smart Citation
“…In a recent study, a two-way paging system sent an average of 3.2 messages per day. 30 In our cell phone group, users responded to 16.6% of reminders, similar to the 14% response rate in the pager study. Thus, it seems unrealistic to expect users to respond to every message received, although participants could have checked their BG level in response to the reminder prompt even if they did not reply to the reminder.…”
Section: Figsupporting
confidence: 69%
“…24 SMS messaging appears ideal for sending and receiving small snippets of data, such as BG values. SMS messages have provided reminders for clinic visits, 25,26 tuberculosis medication compliance, 27 and asthma control, 28,29 as well as diabetes monitoring [30][31][32][33][34][35][36][37][38] in adults. Few studies have focused on teens.…”
mentioning
confidence: 99%
“…Three studies (13,15,16) reported that .70% of participants were Caucasian or non-Hispanic white. In 13 studies, all participants had type 2 diabetes; 3 studies (12,17,18) included participants with both type 1 and type 2 diabetes; the percentage of participants with type 1 diabetes ranged from 19-26%. Six studies (11,17,(19)(20)(21)(22) reported mean duration of diabetes with a range of between 6 and 13 years.…”
Section: Descriptions Of Studiesmentioning
confidence: 99%
“…All of the studies had HbA 1c as an outcome measure and 11 studies (13)(14)(15)(16)(18)(19)(20)(22)(23)(24)(25) provided enough data to combine in a meta-analysis, as shown in Fig. 2.…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%
“…There was a nonsignificant reduction in HbA1c (-0.25 ± 0.94%, p < .10) and mean glucose values (-9.2 ± 25 mg/dl, p = .06) for the 6-month SMS period. Level 2b (limited) evidence from one good quality RCT 51 indicates that a self-managed wireless two-way pager able to send and receive text message reminders may improve metabolic control (average HbA1c decrease of 0.1%-0.3%). The primary outcome of this study was HbA1c, and secondary outcomes were blood pressure, patient perceptions of their disease and health care team, and if the pager system would improve their sense of well-being and adherence to the treatment plan.…”
Section: Cell Phones and Wireless Devicesmentioning
confidence: 99%